Managing Perishable Inventory Systems with Product Returns and Remanufacturing. Issue 6 (29th January 2019) - Fu, Ke; Gong, Xiting; Liang, Guitian
Abstract : Motivated by emerging practice in the cut flower industry, we consider a periodic‐review inventory system for a perishable product with a lifetime of two periods. There are two separate customer demands for the new product with two‐period remaining lifetime and the old product with one‐period remaining lifetime, and a fixed proportion of the unsatisfied demand for one product will purchase the other product as a substitute. One distinctive feature of our system is that a random portion of the sold new product is returned and can be remanufactured and remarketed as the old product for sale. The objective is to maximize the expected total discounted profit over a finite planning horizon. We show that the optimal remanufacturing policy is a modified base–stock policy, and that the optimal manufacturing quantity of the new product decreases in the inventory level of the old product after remanufacturing. Furthermore, when the inventory level of the old product is large, the optimal manufacturing quantity asymptotically approaches a constant, which is lower and upper bounded by two newsvendor fractile solutions. We also conduct a numerical study to derive insights into the effects of remanufacturing and demand substitution. In particular, we show that remanufacturing can be a powerful way of mitigating negative environmental impacts in the cut flower industry. Finally, we discuss two model extensions that allow a joint production capacity and a multi‐period lifetime.